2017
DOI: 10.1136/oemed-2016-104157
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for persistence of lower respiratory symptoms among community members exposed to the 2001 World Trade Center terrorist attacks

Abstract: ObjectivesWe studied the course of lower respiratory symptoms (LRS; cough, wheeze or dyspnoea) among community members exposed to the 9/11/2001 World Trade Center (WTC) attacks during a period of 12–13 years following the attacks, and evaluated risk factors for LRS persistence, including peripheral airway dysfunction and post-traumatic stress disorder (PTSD).MethodsNon-smoking adult participants in a case-control study of post-9/11-onset LRS (exam 1, 2008–2010) were recruited for follow-up (exam 2, 2013–2014).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…The short testing times and ease of administration for subjects are potential advantages in this setting. Oscillometry can be more sensitive than spirometry for detection of airways disease due to occupational exposure [48][49][50][51][52][53][54][55], but this area requires further research.…”
Section: Clinical Settings In Which Oscillometry Is Appliedmentioning
confidence: 99%
“…The short testing times and ease of administration for subjects are potential advantages in this setting. Oscillometry can be more sensitive than spirometry for detection of airways disease due to occupational exposure [48][49][50][51][52][53][54][55], but this area requires further research.…”
Section: Clinical Settings In Which Oscillometry Is Appliedmentioning
confidence: 99%
“…We defined our study population to include those with normal spirometry values. We and others have previously reported the association of small airway dysfunction with symptoms and exposures in many WTC-exposed community members with preserved spirometry [ 16 , 35 , 43 , 44 , 67 ] and we therefore hypothesized that persistent respiratory symptoms would be associated with increased small airway dysfunction in this study. The median values for all measures of forced oscillation, including those considered to assess small airway function (R5–20), were slightly elevated (abnormal) in the group as a whole.…”
Section: Discussionmentioning
confidence: 93%
“…These guidelines included step-up therapy with inhaled corticosteroids (ICS) and eventual addition of long acting bronchodilators (LABAs) to gain control of symptoms. Despite this standardized approach, many patients with WTC exposures continued to report persistent uncontrolled LRS [ 14 , 15 , 16 , 17 ]. Many had spirometry values that were within normal limits despite their continued symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Although they were resolved over time in many exposed residents, symptoms persisted in significant numbers [ 16 , 26 ]. Reasons for response heterogeneity remain elusive, although a recent study of survivors suggested that peripheral airway dysfunction and PTSD may contribute to the persistence of lower respiratory symptoms [ 27 ].…”
Section: Research Portfoliomentioning
confidence: 99%